SSD 쓰기 감소를 위한 2WPR 캐시 페이지 교체 알고리즘 평가 및 개선 - 이형봉(Hyung-Bong Lee); 권기현(Ki-Hyeon Kwon) (디지털콘텐츠학회논문지, 2021)
플래시 메모리 기반 SSD는 기존의 HDD에 비해 접근 속도가 빠르고 가벼우며 물리적 크기가 작다는 장점이 있다. 반면에, 쓰기 전 지우기 연산에 따른 쓰기 팽창 및 지우기 연산 횟수 제한이라는 태생적 단점을 지니고 있다. 플래시 메모리 기반 SSD의 효과적 활용 연구들은 캐시 정책에 의한 쓰기 감소 방안부터 출발한다. 이런 연구 중의 하나로, 최근 2WPR 캐시 페이지 교체 알고리즘이 발표되었다. 이 연구에서는 FTL 환경에서 2WPR 알고리즘을 분석‧평가하고 개선점을 제안하였다. 대규모 현장 트레이스 데이터 기반의 실험 결과, 쓰기 감소 관점에서 개선된 알고리즘의 희생 페이지 선택 기준 지표들이 기존 알고리즘의 지표들보다 약 2% 정도 더 우수하게 반영하는 것으로 나타났다. Flash memory-based SSDs have the advantage of faster access speed, lighter weight and smaller physical size than conventional HDDs. On the other hand, it has inherent disadvantages of amplifying writes and limiting the number of erase operation needed before writing. Therefore, researches for effective use of flash memory-based SSDs start with write reduction scheme based on cache policy. As one of such researches, the 2WPR cache page replacement algorithm was published recently. In a FTL environment, this paper analyzes and evaluates the 2WPR algorithm, and suggests improvements. As a result of the test based on large scale field trace data, it shows that the metrics for victim page selection of the improved algorithm reflect about 2% better than those of the original algorithm in terms of write reduction. KCI Citation Count: 0